Heritage rights that can be registered in favor of the conceived - Samillán Rivera, Aldo Raúl (2020)
Our legislation has regulated the acquisition of heritage rights subject to the condition of the live birth of the conceived; however, its protection under the scope of legal security provided by the registry is not entirely clear. Therefore, the analysis of the figure that regulates article 1 of the Civil Code is of utmost importance to establish guidelines and prior considerations to be taken into account in the preparation of the contract, its registration qualification, and, finally, the registration of the definitive heritage right. In short, these are guidelines that are blurred throughout our regulatory system and it will be compiled in this paper for analysis.